2009
DOI: 10.1681/asn.2008121241
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Maternal Outcomes Among Kidney Transplant Recipients

Abstract: Fertility rates, pregnancy, and maternal outcomes are not well described among women with a functioning kidney transplant. Using data from the Australian and New Zealand Dialysis and Transplant Registry, we analyzed 40 yr of pregnancy-related outcomes for transplant recipients. This analysis included 444 live births reported from 577 pregnancies; the absolute but not relative fertility rate fell during these four decades. Of pregnancies achieved, 97% were beyond the first year after transplantation. The mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
106
2
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 30 publications
12
106
2
11
Order By: Relevance
“…A number of studies comparing allograft survival among pregnant and matched nonpregnant controls found no statistically significant difference in allograft survival between these groups (4,(20)(21)(22)(23)). An analysis of the Australian and New Zealand Dialysis and Transplant Registry reported no difference in 20-year allograft or patient survival between 120 patients who became pregnant after transplantation compared to matched controls (24). Although this study was not limited by voluntary patient participation, it only included pregnancies resulting in live births, and the timing of pregnancy after transplantation was likely later (median 67 months after ESRD start) than in the pregnancies included in our study (24).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A number of studies comparing allograft survival among pregnant and matched nonpregnant controls found no statistically significant difference in allograft survival between these groups (4,(20)(21)(22)(23)). An analysis of the Australian and New Zealand Dialysis and Transplant Registry reported no difference in 20-year allograft or patient survival between 120 patients who became pregnant after transplantation compared to matched controls (24). Although this study was not limited by voluntary patient participation, it only included pregnancies resulting in live births, and the timing of pregnancy after transplantation was likely later (median 67 months after ESRD start) than in the pregnancies included in our study (24).…”
Section: Discussionmentioning
confidence: 80%
“…An analysis of the Australian and New Zealand Dialysis and Transplant Registry reported no difference in 20-year allograft or patient survival between 120 patients who became pregnant after transplantation compared to matched controls (24). Although this study was not limited by voluntary patient participation, it only included pregnancies resulting in live births, and the timing of pregnancy after transplantation was likely later (median 67 months after ESRD start) than in the pregnancies included in our study (24). Overall, 32% of pregnancies in our study ended in early pregnancy loss (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only 3% (a similar proportion to the comparison group) of women developed GDM despite over half taking tacrolimus. Others have also reported low rates of GDM in transplant recipients (4,9), which may be a consequence of different diagnostic blood glucose levels between studies, or the ethnicity of the populations included, but is otherwise unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reporting pregnancy outcome in women with kidney transplants are single-centerbased and retrospective, may span $2 decades, and the majority include ,50 pregnancies (4,5). Four voluntary registers have collected data (6)(7)(8)(9) in larger numbers of women, but are reliant on self-reporting.…”
Section: Introductionmentioning
confidence: 99%
“…This statement is also true for renal transplantation. Although graft survival is quite common during pregnancy, transplant recipients are at a higher risk of obstetric complications, namely, hypertension, urinary tract infections, graft rejection, anemia and gestational diabetes [12,32,33]. Preeclampsia, which does not have any prophylactic interventions to reduce its incidence, develops in more than a quarter of pregnant renal transplant patients, but the diagnosis is difficult in patients who already may have hypertension and proteinuria [34].…”
Section: Discussionmentioning
confidence: 99%